Peritoneal dialysis catheter insertion techniques by the nephrologist - Goh, Bak Leong; Lim, Christopher T. S. (John Wiley and Sons Inc, 2024)
Peritoneal dialysis (PD) catheter is the lifeline of PD patients, and despite the overall strength of the PD program in many countries, PD catheter survival remains the major weakness of the program. The prompt and effective implantation of the PD catheter, as well as speedy management of complications arising from catheter insertion, remains crucial for the success of the program.